Cover Feature: Molecular Switching in Confined Spaces: Effects of Encapsulating the DHA/VHF Photo‐Switch in Cucurbiturils (Chem. Eur. J. 67/2017). Issue 67 (22nd September 2017) - Petersen, Michael Å.; Rasmussen, Brian; Andersen, Nicolaj N.; Sauer, Stephan P. A.; Nielsen, Mogens Brøndsted; Beeren, Sophie R.; Pittelkow, Michael
Abstract : Association of photoswitch within curcubit[7]‐ and ‐[8]uril tunes the kinetics of the thermal isomerization from VHF‐to‐DHA in the photoswitch. The sun setting through the rolling wave symbolizes the aqueous medium in which the photoswitching processes take place. More information can be found in the Full Paper by M. B. Nielsen, S. R. Beeren, M. Pittelkow et al. onpage 17010 .